2013
DOI: 10.1016/j.biortech.2013.07.118
|View full text |Cite
|
Sign up to set email alerts
|

A systematic study of the gaseous emissions from biosolids composting: Raw sludge versus anaerobically digested sludge

Abstract: Volatile organic compound (VOC) and ammonia, that contribute to odor pollution, and methane and nitrous oxide, with an important greenhouse effect, are compounds present in gaseous emission from waste treatment installations, including composting plants. In this work, gaseous emissions from the composting of raw (RS) and anaerobically digested sludge (ADS) have been investigated and compared at pilot scale aiming to provide emission factors and to identify the different VOC families present. CH4 and N2O emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
49
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 31 publications
7
49
0
2
Order By: Relevance
“…Limited values of GWP emissions avoided due to natural gas substitution reported in this study were a consequence of the low value of net energy effectively delivered by the integrated scenarios. A high contribution from the direct emissions of biological process in GWP determination has previously been confirmed in the studies of Blengini [22] and Maulini-Duran et al [52]. Marginal benefits due to carbon sink restoration compared to the direct kgCO2 eq emitted from the biological process were also consistent with References [27,50].…”
Section: Life Cycle Assessment (Lca)supporting
confidence: 72%
See 1 more Smart Citation
“…Limited values of GWP emissions avoided due to natural gas substitution reported in this study were a consequence of the low value of net energy effectively delivered by the integrated scenarios. A high contribution from the direct emissions of biological process in GWP determination has previously been confirmed in the studies of Blengini [22] and Maulini-Duran et al [52]. Marginal benefits due to carbon sink restoration compared to the direct kgCO2 eq emitted from the biological process were also consistent with References [27,50].…”
Section: Life Cycle Assessment (Lca)supporting
confidence: 72%
“…Marginal benefits due to carbon sink restoration compared to the direct kgCO2 eq emitted from the biological process were also consistent with References [27,50]. Similarly, Kim and Kim [23] reported direct GWP emissions from the composting process, about 10 times higher than the emissions avoided due A high contribution from the direct emissions of biological process in GWP determination has previously been confirmed in the studies of Blengini [22] and Maulini-Duran et al [52]. Marginal benefits due to carbon sink restoration compared to the direct kgCO 2 eq emitted from the biological process were also consistent with References [27,50].…”
Section: Life Cycle Assessment (Lca)supporting
confidence: 72%
“…The evolution of organics degradation during sludge composting was mainly demonstrated through three-dimensional excitation-emission matrix spectroscopy (EEM) analysis. Previous studies have demonstrated that NH 3 emissions mainly happened at earlier stage of sludge composting (Szanto et al 2007;Maulini-Duran et al 2013); thus, NH 3 emissions were determined before entering into the maturation phase. The abundance of key functional nitrogen transformation genes involved in microbial nitrification (amoA, nxrA) and denitrification (narG, nirS, nirK, and nosZ) was determined using quantitative PCR (qPCR).…”
Section: Introductionmentioning
confidence: 99%
“…CH 4 produced by sludge is, moreover, combustible, hence giving rise to fire and explosion hazards (Astbury, 2008). Whereas CH 4 emissions from composting and wetlands have been reported before in some papers (e.g., Maulini-Duran et al, 2013;Uggetti et al, 2012), little information is available on the emission of CH 4 during the dewatering process after anaerobic digestion (IPCC, 2002). Additionally, nitrous oxide (N 2 O) has an even higher 100-year global warming potential of 265 (IPCC, 2013), and is released as a by-product of the nitrification and/or denitrification processes.…”
Section: Introductionmentioning
confidence: 97%